2021
DOI: 10.30831/akukeg.901457
|View full text |Cite
|
Sign up to set email alerts
|

School Climate and Self-Efficacy as Predictor of Job Satisfaction

Abstract: In this research, the direct effect of school climate on teacher job satisfaction and the indirect effect of school climate on job satisfaction through self-efficacy were investigated. International Teaching and Learning Survey-2018 data collected by the Organization for Economic Co-operation and Development from Turkish teachers were used in the study. The research data were obtained from the responses of the participants to the Teacher Self-Efficacy, Job Satisfaction and School Climate scales in the Internat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…The teachers who have more access to professional development and are more effective also have a higher level of job satisfaction (Toropova et al, 2020;Hderson, 2022). The relationship between teachers' self-efficacy and job satisfaction has been demonstrated in several studies (Aldridge & Fraser, 2016;Katsantonis, 2021;Türker & Kahraman, 2021;Polatcan & Cansoy, 2019).…”
Section: Conclusion and Discussionmentioning
confidence: 92%
“…The teachers who have more access to professional development and are more effective also have a higher level of job satisfaction (Toropova et al, 2020;Hderson, 2022). The relationship between teachers' self-efficacy and job satisfaction has been demonstrated in several studies (Aldridge & Fraser, 2016;Katsantonis, 2021;Türker & Kahraman, 2021;Polatcan & Cansoy, 2019).…”
Section: Conclusion and Discussionmentioning
confidence: 92%
“…The teachers who have more access to professional development and are more effective also have a higher level of job satisfaction (Toropova et al, 2020;Hderson, 2022). The relationship between teachers' self-efficacy and job satisfaction has been demonstrated in several studies (Aldridge & Fraser, 2016;Katsantonis, 2021;Türker & Kahraman, 2021;Polatcan & Cansoy, 2019).…”
Section: Conclusion and Discussionmentioning
confidence: 92%
“…While SC and teacher's stress level explain 52.3% of teachers' JS, the remaining 47.7% are affected by other variables (Febriantina et al, 2020). There is a direct and positive relationship between the dimensions of school climate, teacher-student relations and participation between stakeholders and JS (Turker & Kahraman, 2021). The meta-analysis results of Kursun and Yilmaz (2020) showed that there is a moderate and significant relationship between SC and JS.…”
Section: Studies On the Factors Associated With Teachers' Jsmentioning
confidence: 99%